PENGARUH STRUKTUR KEPEMILIKAN DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT (SR) - Nur Intan Liesa Pertiwi, (2017)
This research doing to influence test ownership structure variable and from firm size for Sustainability Report (SR) diclosure on Indonesian firm listed in Sustainability Report Award (ISRA) periode 2013 -2015 and that firm listed in Indonesia Stock Exchange (IDX). Population on research as much as 31 sampels of firm. Analysis thecnique using double linear regression and analysis test. Result of research showing partialy (1) Ownership stucture have no significant effect disclosure to sustainability report. (2) firm size haven't significant effect disclose to sustainability report. This limitedness research, resulted digit R insignificant coefficient determination, with the result that independent variables explained varians on limited dependent variables. This study suggest to investor to pay attention to others factors affecting sustainability report before making an investment decision.